Neuromarketing Highlights in How Asperger Syndrome Youth Perceive Advertising - Nuñez-Gomez, Patricia; Alvarez-Ruiz, Anton; Ortega-Mohedano, Felix; Alvarez-Flores, Erika P. (Frontiers in Psychology, 2020)
This study examines how advertising material and brands related to organizational communication are perceived by people with Asperger syndrome, a form of autism. The main objective of the study was to understand whether the perception of advertising differs between individuals with AS and a neurotypical population. Neuromarketing techniques were used to examine two key variables, attention and emotion, which were also measured by physiological and biometric variables. The results were compared with those of a control group from a neurotypical population; i.e., participants who had not been diagnosed with any type of developmental disorder. Commercial advertisements were the preferred material used in this research although social-themed advertisements were also included, some produced by commercial companies and others by institutional advertisers (NGOs and foundations). Qualitative techniques were also used to explain the observed phenomena. Data revealed significant differences between the two groups in their perception of advertising and organizational communication with respect to attention and emotion variables.